Los derechos del consumidor en el Ecuador - Kuri, Daniel; Salas L., Edgar (Nómadas. Critical Journal of Social and Juridical Science, 2015)
Since many years ago negotiation is part of the human being. Historically this activity has evolved and has become an economic push for many nations, several families and individuals. To fight against the abuse of the suppliers of the products or services is required to analyze the actual state of the ¨protection of consumer rights¨ in each country, this is why the following article is intended to inform individuals how the rights of clients work in Ecuador. When it is reviewed Ecuador’s legal system it is important to analyze the results of the laws and to know if they have been applied. This is why this paper studies the functioning of the different state institutions to know the management of food quality and the complaints lodged by consumers.